2017
DOI: 10.1128/jvi.01282-17
|View full text |Cite
|
Sign up to set email alerts
|

Human Metapneumovirus Induces Formation of Inclusion Bodies for Efficient Genome Replication and Transcription

Abstract: Human metapneumovirus (HMPV) causes significant upper and lower respiratory disease in all age groups worldwide. The virus possesses a negative-sense single-stranded RNA genome of approximately 13.3 kb encapsidated by multiple copies of the nucleoprotein (N), giving rise to helical nucleocapsids. In addition, copies of the phosphoprotein (P) and the large RNA polymerase (L) decorate the viral nucleocapsids. After viral attachment, endocytosis, and fusion mediated by the viral glycoproteins, HMPV nucleocapsids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 56 publications
(99 reference statements)
7
76
0
Order By: Relevance
“…In Mononegavirales, transcription and replication takes place in viral factories, e.g. cytoplasmic inclusions where the local concentration of viral proteins is increased thereby facilitating viral replication [53][54][55][56][57][58]. These viral factories, which can be either doublemembrane [59] or membrane-less organelles [60], also likely prevent the activation of host innate immunity by shielding viral proteins and thus impairing their interaction with cellular antiviral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In Mononegavirales, transcription and replication takes place in viral factories, e.g. cytoplasmic inclusions where the local concentration of viral proteins is increased thereby facilitating viral replication [53][54][55][56][57][58]. These viral factories, which can be either doublemembrane [59] or membrane-less organelles [60], also likely prevent the activation of host innate immunity by shielding viral proteins and thus impairing their interaction with cellular antiviral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, we hypothesize that direct cell-to-cell spread of infection might occur in the form of partially assembled viral particles ( Fig 2b ) or nucleocapsids ( Fig 2c ). Interestingly, structures similar to inclusion bodies, which recent studies strongly suggest are organelles involved in replication for several respiratory viruses [ 23 , 24 ], have been observed moving through intercellular extensions [ 5 ]. The potential transfer of a replicative inclusion body from one cell to another ( Fig 2d ) would allow the virus to bypass the first critical hours of infection, and examination of this intriguing hypothesis could alter our understanding of viral spread.…”
Section: The Fast Lanes: What We Don't Knowmentioning
confidence: 99%
“…Similar structures called Negri bodies were initially observed upon rabies virus (RABV) infection and constituted a signature for the diagnosis of the infection ( 6 , 7 ). Since then, it appeared that IBs are a hallmark of infection for many other MNVs such as vesicular stomatitis virus (VSV) ( 8 ), measles virus (MeV) ( 9 ), metapneumovirus (MPV) ( 10 ), Ebola virus ( 11 ), Marburg virus ( 12 ), Nipah virus ( 13 ), and parainfluenza virus (PIV) ( 14 , 15 ). It was shown that these structures are viral factories where all the viral proteins of the polymerase complex concentrate to perform the replication and transcription of the viral genome ( 16 ).…”
Section: Introductionmentioning
confidence: 99%